2011
DOI: 10.1021/ja2065768
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, and Physical Properties of Sterically Unprotected Hydrocarbon Radicals

Abstract: We have prepared and isolated neutral polycyclic hydrocarbon radicals. A butyl-substituted radical gave single crystals, in which a π-dimeric structure, not a σ-bonded dimer, was observed, even though steric protection was absent. Thermodynamic stabilization due to the highly spin-delocalized structure contributes effectively to the suppression of σ-bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 33 publications
3
82
0
Order By: Relevance
“…This is significantly larger than the π-stacking separation found in planar hydrocarbon radicals (≈3 Å), for which recent studies revealed a combination of strong SOMO–SOMO overlap with dispersion forces giving rise to the so-called multicenter bonding configuration. 9,3739 Thus, a direct magnetic interaction (overlap) is unlikely to contribute to the attractive interaction of radicals in the self-assembled BDPA chains on Au(111).…”
Section: Resultsmentioning
confidence: 99%
“…This is significantly larger than the π-stacking separation found in planar hydrocarbon radicals (≈3 Å), for which recent studies revealed a combination of strong SOMO–SOMO overlap with dispersion forces giving rise to the so-called multicenter bonding configuration. 9,3739 Thus, a direct magnetic interaction (overlap) is unlikely to contribute to the attractive interaction of radicals in the self-assembled BDPA chains on Au(111).…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, I succeeded in the isolation of a cation species of 8 , and after coming back to Japan, I continued this research and finally isolated an n ‐butyl derivative of 8 in a crystalline form. X‐ray crystallographic analysis revealed that the radical exists in a discrete form in the solid state (Figure ) . This is the first hydrocarbon radical that can survive in the solid state only by thermodynamic stabilization.…”
Section: Phenalenylmentioning
confidence: 99%
“…[8] In both DT 2 and PT 2 ,t he CÀC bonds connecting the monomers are remarkably longer (1.638(2) for DT 2 and 1.633(10) and 1.653(10) for PT 2 ) than au sual C(sp 3 ) À C(sp 3 )b ond (1.54 ). [14][15][16][17][18][19] Figure 3cshows the bond lengths in JDC determined by X-ray analysis. In ac loser radical pair, there are nine intermolecular short contacts between sp 2 carbon atoms,which are even shorter than the van der Waals contact of sp 2 carbon atoms (3.4 ;F igure 3b).…”
mentioning
confidence: 99%